2019
DOI: 10.1155/2019/5432301
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Human Amniotic Epithelial Cells on Injuries and Disorders in the Central Nervous System

Abstract: Despite recent advances in neurosurgery and pharmaceuticals, contemporary treatments are ineffective in restoring lost neurological functions in patients with injuries and disorders of the central nervous system (CNS). Therefore, novel and effective therapies are urgently needed. Recent studies have indicated that stem cells, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and mesenchymal stem cells (MSCs), could repair/replace damaged or degenerative neurons and improve function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 92 publications
(122 reference statements)
0
49
0
Order By: Relevance
“…NSCs contribute to the repair of neuronal function in brain tissue, but because they are low in number and have a limited distribution range in the brain, NSCs exhibit a limited capacity for repairing neural damage [59]. Vascular endothelial growth factor (VEGF)-mediated effects on vascular endothelial cells include accelerated proliferation and migration of NSCs, the formation of new blood vessels, and an increase in vascular permeability [59].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…NSCs contribute to the repair of neuronal function in brain tissue, but because they are low in number and have a limited distribution range in the brain, NSCs exhibit a limited capacity for repairing neural damage [59]. Vascular endothelial growth factor (VEGF)-mediated effects on vascular endothelial cells include accelerated proliferation and migration of NSCs, the formation of new blood vessels, and an increase in vascular permeability [59].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…NSCs contribute to the repair of neuronal function in brain tissue, but because they are low in number and have a limited distribution range in the brain, NSCs exhibit a limited capacity for repairing neural damage [59]. Vascular endothelial growth factor (VEGF)-mediated effects on vascular endothelial cells include accelerated proliferation and migration of NSCs, the formation of new blood vessels, and an increase in vascular permeability [59]. Studies have reported that transplantation of VEGF-transfected NSCs can be administered to treat cerebral ischemia in adult rats; NSCs have been discovered to migrate to the host brain tissue and express VEGF gene products [59].…”
Section: Neural Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations